Tensions in Human-Technology Research - Häkkinen, Päivi (Human Technology, 2012)
As I begin my tenure as editor in chief of Human Technology: An Interdisciplinary Journal of Humans in ICT Environments, I am pleased both personally and professionally to continue building the significance of this journal in the scientific literature of many research fields. The founding editor in chief, Professor Pertti Saariluoma, has contributed greatly to defining the basis for the scope of Human Technology. During his editorial tenure, the papers published in the journal have addressed a wide variety of questions related to human–technology research. Earlier issues of the journal have covered research on mobile communication, innovations, ICT and education, human technologies for special needs, games and smart environments, culture, creativity and technology, distributed leadership and on-line communities, design-use relationships, cognition and HCI, psychology of programming, and creativity in software design. This variety of fields and topics certainly illustrates the multidisciplinary nature of human– technology research. In the inaugural issue of the journal, Professor Saariluoma stated that becoming familiar with the wide variety of questions at the intersection of humans and technology and the potential solutions demands exploration irrespective of the field of research (Saariluoma, 2005). Clearly, no single theory or particular approach will solve the totality of human–technology problems (e.g., the grand challenges or “wicked problems” in many societies). One of the guiding principles in multidisciplinary research, therefore, has been to foster and support openness towards multiple schools of thoughts (Stahl & Hesse, 2011).